Types of intermittent fasting and their effects on obesity and type II diabetes mellitus - Shu, Xian Gan; Patricia, Karissa; Yong, Ling Sou; Hui, Ching Low; Teck, Yew Low; Simpson, Timothy; Pei, Paulina Suu Tan; Pey, Yee Lee; Shamsul Mohd Zain,; Wickneswari Ratnam, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Obesity and type II diabetes mellitus affect millions of people both in Malaysia and worldwide due to sedentary lifestyles and unhealthy diets. Intermittent fasting reduces calorie intake by interweaving eating periods with prolonged fasting periods on a recurring basis. Therefore, it could be a potential solution to induce weight loss, leading to improved blood glucose level as observed in type II diabetes mellitus individuals. However, its feasibility remains unclear. This review aimed to compare the beneficial effects and adverse reactions from different types of intermittent fasting in obese and type II diabetes mellitus studies. The review was carried out by combing through several online databases. Keywords such as “Intermittent fasting”, “Obesity”, “Type II Diabetes Mellitus” were used and relevant articles were selected. The findings of this review showed that intermittent fasting is feasible and effective in reducing body weight and improving blood glucose. The beneficial effects of intermittent fasting appear to outweigh the adverse reactions. Having said that, intermittent fasting is unsuitable for individuals with packed schedules and certain health conditions such as pregnancy. This review will hopefully shed light on intermittent fasting as a potential intervention to combat obesity and type II diabetes mellitus. Further exploration of intermittent fasting could reduce both the morbidity and mortality rates from non-communicable diseases globally.